Enhancement of no-reference image quality assessment for contrast-distorted images using natural scene statistics features in Curvelet domain - Ahmed I.T.; Der C.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Image enhancement; Systems engineering; Curvelets; Distorted images; Feature fusion method; Feature selection methods; Image quality assessment (IQA); K fold cross validations; Natural scene statistics; No-reference image quality assessments; Image quality